PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMP TAMAN DEWASA IBU PAWIYATAN YOGYAKARTA - Eni Ayu Lestari (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
This aims of the study were to know the tendency of science learning outcomes of students class VII in SMP Taman Dewasa Ibu Pawiyatan Yogyakarta 2014/2015 which were taught using cooperative learning Think Pair Share (TPS) and Comparative conventional. Comparatively was to know the effect of using cooperative learning Think Pair Share (TPS) in science learning outcomes of students class VII in SMP Taman Dewasa Ibu Pawiyatan Yogyakarta 2014/2015. The result showed that the tendency of science learning outcomes of students who were taught using Think Pair Share (TPS) model is higher than using conventional. The result showed that there was the influence of cooperative learning Think Pair Share (TPS) on science learning outcomes of students class VII in SMP Taman Dewasa Ibu Pawiyatan Yogyakarta 2014/2015.